Prosocial deficits in behavioral variant frontotemporal dementia relate to reward network atrophy. Issue 10 (14th September 2017) - Sturm, Virginia E.; Perry, David C.; Wood, Kristie; Hua, Alice Y.; Alcantar, Oscar; Datta, Samir; Rankin, Katherine P.; Rosen, Howard J.; Miller, Bruce L.; Kramer, Joel H.
Abstract: Introduction: Empathy and shared feelings of reward motivate individuals to share resources with others when material gain is not at stake. Behavioral variant frontotemporal dementia (bvFTD) is a neurodegenerative disease that affects emotion‐ and reward‐relevant neural systems. Although there is diminished empathy and altered reward processing in bvFTD, how the disease impacts prosocial behavior is less well understood. Methods: A total of 74 participants (20 bvFTD, 15 Alzheimer's disease [AD], and 39 healthy controls) participated in this study. Inspired by token‐based paradigms from animal studies, we developed a novel task to measure prosocial giving (the "Giving Game"). On each trial of the Giving Game, participants decided how much money to offer to the experimenter, and prosocial giving was the total amount that participants gave to the experimenter when it cost them nothing to give. Voxel‐based morphometry was then used to identify brain regions that were associated with prosocial giving. Results: Prosocial giving was lower in bvFTD than in healthy controls; prosocial giving in AD did not differ significantly from either of the other groups. Whereas lower prosocial giving was associated with atrophy in the right pulvinar nucleus of the thalamus, greater prosocial giving was associated with atrophy in the left ventral striatum. Conclusion: These findings suggest that simple acts of generosity deteriorate in bvFTD due to lateralized atrophy in reward‐relevant neural systems that promote shared feelings of positive affect. Abstract : We found that prosocial giving is diminished in behavioral variant frontotemporal dementia, a neurodegenerative disease that impacts emotion and social behavior. Lower prosocial giving was associated with lower gray matter volume in brain regions that support reward processing and positive emotion.